All Focus is Contrastive: On Polarity (Verum) Focus, Answer Focus, Contrastive Focus and Givenness. (22nd January 2022) - Goodhue, Daniel
Abstract: I develop a general theory of focus and givenness that can account for truly contrastive focus, and for polarity focus, including data that are sometimes set apart under the label "verum focus". I show that polarity focus creates challenges for classic theories of focus (e.g. Rooth 1992, a.o.) that can be dealt with by requiring that all focus marking is truly contrastive, and that givenness deaccenting imposes its own distinct requirement on prominence shifts. To enforce true contrast, I employ innocent exclusion (Fox 2007 ), which I suggest may impose a general filter on what counts as a valid alternative. A key, novel feature of my account is that focal targets are split into two kinds, those that are contextually supported and those that are constructed ad hoc, and that the presence of a contextually supported target can block the ability to construct an ad hoc target. This enables a novel explanation of the data motivating true contrast, and enables polarity focus to be brought into the fold of a unified and truly contrastive theory of focus. I then compare the account to theories of verum focus that make use of non-focus-based verum operators, and make the argument that the focus account is more parsimonious and has better empirical coverage.